2022
DOI: 10.1159/000530171
|View full text |Cite
|
Sign up to set email alerts
|

SHOX Whole Gene Duplications Are Overrepresented in SHOX Haploinsufficiency Phenotype Cohorts

Abstract: Transcription of SHOX is dependent upon the interaction of the gene with a complex array of flanking regulatory elements. Duplications that contain flanking regulatory elements but not the SHOX gene have been reported in individuals with SHOX haploinsufficiency syndromes, suggesting that alterations to the physical organisation or genomic architecture may affect SHOX transcription. Individuals with tall stature and an additional X or Y chromosome have an extra copy of both the SHOX gene and the entire SHOX r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Conversely, the augmented body height could plausibly be attributed to an overexpression of growth-associated genes, such as short stature homeobox (SHOX), given that individuals with 47,XXY karyotypes harbor three copies of this gene [91]. An extra copy of the SHOX gene and all associated regulatory elements would be expected to determine overexpression; nevertheless, duplications of the entire SHOX gene but only part of the regulatory region have no certain genotype-phenotype correlations, exhibiting a wide range of possible phenotypes [92]. Moreover, Tropeano et al (2016) demonstrated that SHOX microduplications represent a low penetrance risk factor for autism spectrum disorders and related neurodevelopmental conditions in males and females [93].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the augmented body height could plausibly be attributed to an overexpression of growth-associated genes, such as short stature homeobox (SHOX), given that individuals with 47,XXY karyotypes harbor three copies of this gene [91]. An extra copy of the SHOX gene and all associated regulatory elements would be expected to determine overexpression; nevertheless, duplications of the entire SHOX gene but only part of the regulatory region have no certain genotype-phenotype correlations, exhibiting a wide range of possible phenotypes [92]. Moreover, Tropeano et al (2016) demonstrated that SHOX microduplications represent a low penetrance risk factor for autism spectrum disorders and related neurodevelopmental conditions in males and females [93].…”
Section: Discussionmentioning
confidence: 99%